(untitled) (Revista de História da UEG (REVHIST), 2024)
The Provisional Governments of Pernambuco and Paraíba, during the expansion of the Pernambucan Revolution (1817), devised a plan of attack on the village of Icó-CE, which, in fact, never occurred. This study aims to understand the dynamics of this plan, which includes those involved in its elaboration, the strategic and tactical content, how the mobilization of troops worked, and, of course, the possible reasons that led to its non-execution. We employed a relational analysis of the documents of the Devassa of Crime of Lesa-majesty, complemented with elements of Discourse Analysis to examine both the explicit content and the implicit subtexts and contexts. We concluded that: the plan involved the mobilization of three armed regiments, one from Crato-CE led by José Martiniano Pereira de Alencar and José Pereira Filgueiras, one from Souza-PB and Pombal-PB under the command of Miguel Joaquim César de Melo and one from the Serra do Martins, from Portalegre-RN, commanded by David Leopoldo Targini; the analysis suggests that the military pressure of the Paraiban royalists and the power dynamics in the backlands created a political obstacle to the non-execution of the plan: the loss of support from Father Luís José Correia de Sá. Keywords: Pernambucan Revolution. Icó. Ceará.